Lithographically Designed Conical Microcarriers for Programed Release of Multiple Actives - Je, Kwanghwi; Kim, Ju Hyeon; Shim, Tae Soup; Ku, Minhee; Yang, Jaemoon; Kim, Shin Hyun (Advanced Materials Interfaces, 2018)
The programed release of multiple ingredients is important in the therapeutics and pharmaceutical fields. A variety of core–shell microcarriers have been designed to fulfill the release function; however, encapsulating multiple actives in their own compartments and releasing them in a programed manner remains a challenge due to restrictions on the material sets that may be used to form the compartments. In this work, the development of lithographically featured core–shell microcarriers composed of double cones and a cap that encapsulate and release various combinations of multiactives in a predefined fashion is reported. Active-free caps are first prepared on a photomask using conventional photolithography. Onto each cap, sequentially, an active-loaded small cone and large cone in two steps of reaction–diffusion-mediated photolithography (RDP) are formed. The release kinetics of the actives stored in the inner and outer cones are controlled by tailoring the crosslinking density of the photocured polymers that composed each compartment. The cap prevents direct diffusion from the inner cone to the surrounding. The RDP-based lithographic means for creating core–shell microcarriers provides new opportunities for delivering synergistic combinations of drugs in pharmacotherapy.
Keywords: core–shell; microcarriers; photolithography; programed release; reaction–diffusion